A Case Report of Malaria with Concurrent Dengue and Typhoid Fever - Andi Kartini Eka Yanti; Andi Zul Tasyriq; Hendrian Chaniago (International Medical Journal Corp. Ltd, 2025)
Introduction: In Indonesia, malaria, dengue fever (DF), and typhoid fever are endemic infectious diseases that remain major public health concerns. Data from the Ministry of Health in 2025 show high incidence rates of these three diseases, especially in Papua, Bali, and urban areas, which increase the risk of coinfection and complicate diagnosis and treatment. Methods: A case is reported of an 18-year-old man presenting with high fever, headache, nausea, and thrombocytopenia. Initial serological and laboratory tests indicated dengue fever and typhoid infection. Routine monitoring and peripheral blood examination were performed and malaria co-infection was detected. Results: The patient's fever and platelets continued to decrease despite being given supportive therapy and antibiotics. Peripheral blood smear confirmed Plasmodium falciparum infection, prompting the addition of antimalarial therapy with dihydroartemisinin-piperaquine and primaquine. Following comprehensive treatment and close monitoring, the patient’s condition improved, with normalization of vital signs and increased platelet count. Conclusion: Coinfection of malaria, dengue fever, and typhoid in Indonesia is rare but requires special attention. Systematic diagnosis and intensive monitoring are essential for effective treatment and prevention of complications. Increased clinical awareness of possible multiple infections in febrile patients in endemic areas can improve prognosis and optimize patient management.